Propuesta metodológica para la gestión turística sostenible de humedales, caso de estudio La Segua, Manabí, Ecuador - Tuárez Intriago, Odalis Lizbeth (2021)
The objective of the research was to make a methodological proposal for the sustainable tourism environmental management of wetlands, La Segua case study, Manabí province. The methods used were analytical-synthetic. To achieve the study objectives, a methodology was structured that began in its first phase with an environmental and tourist diagnosis, where an environmental and tourist characterization of the wetland was carried out, as well as the current management, while the strategic analysis through the application of a SWOT matrix. In the second phase it was based on determining the knowledge of the management of the social actors of the wetland, through the application of surveys and interviews with community members, among others, as well as a matrix of stakeholders for the subsequent determination of strategic solutions. The third phase consisted in the establishment of a methodology for the environmental and tourist management of La Segua wetland through the application of the 5W2H matrix, which allowed the structuring of three programs: 1. Strengthening of the local capacity for environmental management; 2. Territorial reorganization and empowerment of the wetland as a regional tourist attraction; and 3. Strengthening of public management among tourist, local and regional actors. 11 strategic projects constitute the three programs, which will contribute to the sustainable environmental and tourism management of the La Segua wetland. Finally, the investigation showed the tourist potential of the wetland, as well as the shortcomings that exist in public and private management, such as maintenance of infrastructure, poor marketing and sustainable management. On the other hand, the research contributed with the proposal of strategies to generate alternative solutions aimed at the sustainable development of tourism in La Segua wetland.